Musa cavendish ameliorates isoproterenol-induced renal and hepatic injury in Wistar rats - Emuesiri Kohworho Umukoro; Erhiori Akponah; Oghenekparobor Blessing Elijah; Emuesiri Goodies Moke; John O. Ohaju-Obodo; Abraham Georgewill (Orapuh Journal)
Introduction